Tautomerase Activity-Lacking of the Macrophage Migration Inhibitory Factor Alleviates the Inflammation and Insulin Tolerance in High Fat Diet-Induced Obese Mice - Li, Yan-Hong; Wen, Ke; Zhu, Ling-Ling; Lv, Sheng-Kai; Cao, Qing; Li, Qian; Deng, Libin; Chen, Tingtao; Wang, Xiaolei; Deng, Ke-Yu; Wang, Ling-Fang; Xin, Hong-Bo (Frontiers in Endocrinology, 2020)
Macrophage migration inhibitory factor (MIF) has multiple intrinsic enzymatic activities of the dopachrome/phenylpyruvate tautomerase and thiol protein oxidoreductase, and plays an important role in the development of obesity as a pro-inflammatory cytokine. However, which enzymatic activity of MIF is responsible for regulating in obesity are still unknown. In the present study, we investigated the roles of the tautomerase of MIF in high fat diet (HFD)-induced obesity using MIF tautomerase activity-lacking (MIFP1G/P1G) mice. Our results showed that the serum MIF and the expression of MIF in adipose tissue were increased in HFD-treated mice compared with normal diet fed mice. The bodyweights were significantly reduced in MIFP1G/P1G mice compared with WT mice fed with HFD. The sizes of adipocytes were smaller in MIFP1G/P1G mice compared with WT mice fed with HFD using haematoxylin and eosin (H&E) staining. In addition, the MIFP1G/P1G mice reduced the macrophage infiltration, seen as the decreases of the expression of inflammatory factors such as F4/80, IL-1β, TNFα, MCP1 and IL-6. The glucose tolerance tests (GTT) and insulin tolerance tests (ITT) assays showed that the glucose tolerance and insulin resistance were markedly improved, and the expressions of IRS and PPARγ were upregulated in adipose tissue from MIFP1G/P1G mice fed with HFD. Furthermore, we observed that the expressions of Bax, a pro-apoptotic protein, and the cleaved caspase 3-positive cells in white tissues were decreased and the ratio of Bcl2/Bax was increased in MIFP1G/P1G mice compared with WT mice. Taken together, our results demonstrated that the tautomerase activity-lacking of MIF significantly alleviated the HFD-induced obesity and adipose tissue inflammation, and improved insulin resistance in MIFP1G/P1G mice.